A history of the Jewish people in the time of Jesus Christ ... - Schürer, Emil (Clark's foreign theological library. N.S, 1885)
Div.1, v.1-2. Political history of Palestine, from B.C. 175 to A.D. 135 -- Div.2, v.1-3. The internal condition of Palestine, and of the Jewish people, in the time of Jesus Christ.